2012
DOI: 10.7150/ijms.4514
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 21 Inhibits Left Ventricular Remodeling in the Early Phase of Rat Model with Ischemia-reperfusion Injury by Suppressing Cell Apoptosis

Abstract: Objective: To determine the role of microRNA 21(miR-21) on left ventricular remodeling of rat heart with ischemia-reperfusion (I/R) injury and to investigate the underlying mechanism of miR-21 mediated myocardium protection.Methods: Rats were randomly divided into three groups: an I/R model group with Ad-GFP (Ad-GFP group), an I/R model group with Ad-miR-21 (Ad-miR-21 group) and a sham-surgery group. Changes in hemodynamic parameters were recorded at 1 week after I/R. Histological diagnosis was achieved by hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 37 publications
2
55
0
1
Order By: Relevance
“…Elevated miR-21 expression may induce cardiac hypertrophy and fibrosis by increasing the secretion of fibroblast growth factor-2, thereby inhibiting the apoptosis of cardiac fibroblasts [33]. miR-21 upregulation during the early phase of ischemia-reperfusion injury has been shown to attenuate cardiomyocyte apoptosis [34]. Moreover, miR-21 has been reported to attenuate the death of ischemic cortical neurons by reducing the expression of the FasL (Fas ligand) gene [35].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated miR-21 expression may induce cardiac hypertrophy and fibrosis by increasing the secretion of fibroblast growth factor-2, thereby inhibiting the apoptosis of cardiac fibroblasts [33]. miR-21 upregulation during the early phase of ischemia-reperfusion injury has been shown to attenuate cardiomyocyte apoptosis [34]. Moreover, miR-21 has been reported to attenuate the death of ischemic cortical neurons by reducing the expression of the FasL (Fas ligand) gene [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic examination: Hemodynamic examination was performed as previously described. 8) Hemodynamic parameters, including the heart rate (HR), left ventricular end-diastolic pressure (LVEDP), left ventricular systolic pressure (LVSP), maximal rate of rise in blood pressure in the ventricular chamber (+dp/dt max), and maximal rate of decline in blood pressure in the ventricular chamber (-dp/dt max) were measured and recorded by an 8-channel polygraph system (RM-6000). RNA extraction and qRT-PCR analysis: Total RNA was obtained separately from the infarcted, border, and non-infarcted areas of the LV at 24 hours after LAD ligation, as well as from the sham group at the same time.…”
Section: Measurement Of the Dimensions Of The Left Ventricles (Lv) Andmentioning
confidence: 99%
“…6) Our previous studies have shown that miR-21 plays an important role in the protection of heart function and is a possible mechanism in ischemic disease. 7,8) By analyzing conserved miRNAs that were upregulated in a rat AMI model, we identified miR-214 as a sensitive marker of ischemic injury. 7) In the current study, we designed a rat AMI model with the aim of investigating whether miR-214 had a protective effect on heart function.…”
mentioning
confidence: 99%
“…Furthermore, subsequent reoxygenation may further aggravate the damage (6). Multiple miRNAs have been shown to function as protectors against hypoxia/reoxygenation (H/R)-induced myocardial injury (7)(8)(9). However, the specific molecular mechanisms underlying this effect have remained elusive.…”
Section: Introductionmentioning
confidence: 99%